2008
DOI: 10.4049/jimmunol.180.3.1390
|View full text |Cite
|
Sign up to set email alerts
|

Human Follicular Dendritic Cells Interact with T Cells via Expression and Regulation of Cyclooxygenases and Prostaglandin E and I Synthases

Abstract: PGE2 inhibits mature T cell proliferation and protects T cells from activation-induced cell death (AICD). We have previously demonstrated that human follicular dendritic cells (FDC) strongly express PGI synthase. In this study, the hypothesis that FDC have regulatory roles on germinal center T cells by controlling production of PGE2 and PGI2 was tested. Confocal microscopic analyses of human tonsil tissues revealed that FDC indeed expressed PGE synthase in addition to PGIS. To confirm these results, we studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 46 publications
3
38
0
1
Order By: Relevance
“…Because B cells were incubated with beraprost before the further culture with T cells, one may suspect that the residual beraprost might have influenced the enhanced proliferation. This is unlikely according to our previous results that showed a suppression of T cell proliferation by beraprost (11,39). Considering the fact that GC T cells do not normally proliferate and produce IL-2 in response to Ag stimulation (40)(41)(42), there must be a balance between positive and negative signals for cellular proliferation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Because B cells were incubated with beraprost before the further culture with T cells, one may suspect that the residual beraprost might have influenced the enhanced proliferation. This is unlikely according to our previous results that showed a suppression of T cell proliferation by beraprost (11,39). Considering the fact that GC T cells do not normally proliferate and produce IL-2 in response to Ag stimulation (40)(41)(42), there must be a balance between positive and negative signals for cellular proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…Considering the fact that GC T cells do not normally proliferate and produce IL-2 in response to Ag stimulation (40)(41)(42), there must be a balance between positive and negative signals for cellular proliferation. In this balance control, FDCs appear to have a dominating role by providing prostacyclin and PGE 2 (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FDCs accumulate administered Ags on their surface in the form of immune complexes, which act as selection ligands for GC B cells bearing diversified BCRs. Additionally, it has been reported that our FDC line (20), human FDC lines established by other laboratories (39), and FDCs isolated from lymphoid tissues (40) all expressed PGE synthase. Thus, PGE 2 production is considered to be a characteristic feature of FDCs.…”
Section: Discussionmentioning
confidence: 99%